Investment development of Ukraine in the context of world financial crisis on national economy - Vitaliy Zapukhlyak (Cхід, 2013)
The article explores trends in investment countries, including Ukraine, post-crisis period. Analysis of investment climate in Ukraine and the main factors that destimulate investment activity. The directions of increase of investment attractiveness of Ukraine's economy to foreign investors.